Communication for International Careers 1 - POP-FLANJA, Delia (Presa Universitară Clujeană, 2021)
The general objective of the course Communication for International Careers 1 is to acquaint students with professional elements pertaining to written and oral communication in English, for the purpose of offering them the skills necessary to develop international careers. Some of the most important specific objectives are to develop the range of vocabulary utilized by students in the process of communicating, to increase students’ adaptability to a wide range of communication situations and to develop practical abilities which are needed to participate in complex communication situations.